New Platinum(II) Complex Containing Asymmetric Tetra Dentate Schiff Base Ligand Synthesis, Characterization and DFT Calculation - Alireza Akbari; Iran Sheikhshoaie; Lotfali Saghatforoush; S. Yousof Ebrahimipour; Zohreh Amiri (E-Journal of Chemistry)
The tetra dentate neutral (E)-4-nitro-2-((2-(2-(pyridin-2-yl) ethylthio) ethylimino) methyl) phenol, (pytaO2NSalH), Schiff-base ligand was synthesized using 1-(2-pyridyl)-3-thia-s-aminopentane (pyta) and 5-NO2 salicylaldehyde. Then the related square planar Pt (II) cationic complex, [Pt (NSNO)] Cl, was synthesized using PtCl2 (SMe2)2 as precursor complex. The nature of the pytaO2NSalH and its platinum complex were determined by the elemental analysis, molar conductivity and spectrochemical (IR, UV–vis, 1HNMR) techniques. In addition, the fully optimized geometries and vibration frequencies of them together were calculated using the ADF 2009.01 package. Structural parameters are in good agreement with the experimental data. The calculated and experimental results confirmed the suggested structures for the ligand and complex.